An Assessment of The English Reading Comprehension Strategies Utilized by Level-One Students at A South African University - Vincent Ndishunwani Demana; Mzamani Johannes Maluleke; Ramos Asafo-Adjei; Thifhelimbilu Emmanuel Sikitime; Ernest Kwesi Klu (Journal of English Language Studies, 2024)
The researchers examined the approaches employed by first-year students at a university in South Africa to comprehend English reading material. The study used a combination of quantitative and qualitative research methods, involving 309 first-year students from various departments who were taking the English Communication Skills course. Data was gathered using a self-administered questionnaire, the Survey of Reading Strategies (SORS) developed by Mokhtari and Sheorey. The researchers used descriptive statistics, such as frequency, percentage, mean, standard deviation, and usage level, to analyze the frequency of each reading strategy. The findings underscore the significance of offering guidance on reading comprehension strategies to assist first-year students in managing the rigorous academic demands of university and to teachers and lecturers in helping their students learn to become constructively responsive and thoughtful readers, which will promote academic reading skills and ultimately enhance academic achievement.